2005
DOI: 10.1111/j.1551-2916.2005.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Ti3SiC2

Abstract: The present contribution reports the unlubricated friction and wear properties of Ti3SiC2 against steel. The fretting experiments were performed under varying load (1–10 N) and the detailed wear mechanism is studied using SEM‐EDS, Raman spectroscopy, and atomic force microscopy. Under the selected fretting conditions, Ti3SiC2/steel tribocouple exhibits a transition in friction as well as wear behavior with coefficient of friction varying between 0.5 and 0.6 and wear rate in the order of 10−5 mm3·(N·m)−1. Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 11 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…Gupta et al [15] indicated that the tribofilms resulted in low (<10 À6 mm 3 N À1 m À1 ) wear rates and friction coefficients <0.5. The results in this research were similar to that observed by Sarkar et al [26] and Gupta et al [14,15]. The glazes actually had not only a significant antifriction effect, but also a protective action for the friction surfaces.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Gupta et al [15] indicated that the tribofilms resulted in low (<10 À6 mm 3 N À1 m À1 ) wear rates and friction coefficients <0.5. The results in this research were similar to that observed by Sarkar et al [26] and Gupta et al [14,15]. The glazes actually had not only a significant antifriction effect, but also a protective action for the friction surfaces.…”
Section: Discussionsupporting
confidence: 92%
“…The contents of C, O, Al, Si, Ti and Fe were 32.38 at.%, 32.18 at.%, 1.41 at.%, 6.68 at.%, 16.48 at.% and 10.86 at.%, respectively. It showed that the wear debris was composed of oxides, Ti 3 SiC 2 and Sarkar et al [26] investigated the unlubricated friction and wear properties of Ti 3 SiC 2 against steel. The results showed that under the selected fretting conditions, Ti 3 SiC 2 /steel tribocouple exhibited a transition in friction as well as wear behavior with coefficient of friction varying between 0.5 and 0.6 and wear rate in the order of 10 À5 mm 3 N À1 m À1 .…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to associate the higher friction coefficient of contact surfaces with its lower CNC concentrations, which can induce severe damages of a thin near surface layer [40], thus resulting in the extensive removal of materials occurring layer by layer. This phenomenon can be attributed to the fact that a greater extent of plastic deformation and exfoliation induced by asperity junctions [41,42] and interface adhesions [43] as a result of friction mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In another work, delaminations, deformation of individual grains, grain pull out have been observed in the area of indentations (El-Raghy et al, 1999). The oxide formation and subsequent increase of flexural strength up to 1000 • C could be observed, however, the strength dramatically reduces at 1200 • C. The strength of oxidized Ti 3 SiC 2 specimen is influenced by two components; residual compressive stress due to the formation of oxide phase and strength due to the oxide thickness (Sarkar et al, 2005). The calculated residual stress of T 3 and strength of oxide phase are ∼876 and ∼173 MPa, respectively (Bao et al, 2007;Sarkar et al, 2007b,c).…”
Section: Methodsmentioning
confidence: 95%
“…Detail processing procedure could be found elsewhere (Sarkar et al, 2005(Sarkar et al, , 2007a. Disks were then machined into flexural specimens of 3 mm × 4 mm × 40 mm and separately heat-treated at 700, 1000 and 1200 • C for 2 h in air and the samples were designated as T 2 , T 3 and T 4 , respectively; whereas original sample was denoted as T 1 .…”
Section: Methodsmentioning
confidence: 99%